Effect of stocking density on survival and growth of endangered snakehead (Channa striatus) in tank culture - Asruri, Subaidi (2012)
Growth performance and survival of C. striatus at different stocking densities in tank were investigated. The three different stocking densities were used in this experiment, 20pcs/m2, 30 pcs/m2 and 40 pcs/m2. There were three replicates for each treatment. Fingerlings were reared for 18 weeks in tank size 2.5m x 1.3m x 0.75m and given formulated feed 43% of protein twice a day with 6% of body weight. Water quality parameters were measured every week during the experiment. Results showed that there was significant difference (P< 0.05) on growth among the treatments. The growth performance was significantly higher in T1 than in T2 and T3. However, the survival rate showed no significant difference (P< 0.05) among all the treatments. The food conversion ratio (FCR) value among the treatments was significantly lower (P<0.05) in T1 than T2 and T3. Therefore, the highest growth and FCR of C. striatus culture was with stocking densities 20 pcs/m2. Water quality measurements range for temperature, DO, pH and ammonia is 26.3-26.57 ⁰C, 5.15-5.27 mg/L, 6.32-6.92, 0.91-1.73 mg/L respectively.